Cardioprotective Properties of Ginkgo Biloba Extract 80 via the Activation of AKT/GSK3β/β-Catenin Signaling Pathway - Zheng, XiangWei; Gao, Qi; Liang, Shuang; Zhu, GuoQin; Wang, DanDan; Feng, Yi (Frontiers in Molecular Biosciences, 2021)
Elderly people are more likely to experience myocardial infarction (MI) than young people. And the elderly have worse post-MI mortality and prognosis than the young. Ginkgo biloba extract 50 (GBE50) is a standardized oral GBE product that matches the standardized German product, EGb761, which has been used to treat acute myocardial infarction (AMI). This explorative study was undertaken to form a new injection from GBE50 and improve the purity of its components to form GBE80, and to investigate the effect of GBE80 on AMI. Ginkgo biloba extract 80 (GBE80) is a novel injection that was prepared by mixing Ginkgo flavonoids and lactones in a 4:1 weight ratio, with a content of more than 80%. A Cell Counting kit-8 was used to determine the biological safety and protective effect of GBE80 on cardiomyocytes against oxidative damage. The aged AMI rat model was developed and used to determine the myocardial infarction weight ratio using triphenyltetrazolium chloride staining. Terminal deoxynucleotidyl transferase-mediated dUTP-biotin nick end labeling was applied to detect cell apoptosis in myocardial tissue. Western blotting and immunohistochemistry were used to measure the protein levels of members of the AKT/GSK3β/β catenin pathway in vitro and in vivo, respectively. In vitro, GBE80 suppressed H2O2-induced cytotoxicity by promoting AKT/GSK3β/β catenin signaling, while it did not show cytotoxicity to normal cardiomyocytes in the 0–500 µg/mL dose range. After 7 days of administration to aged AMI rats, GBE80 markedly reduced the weight ratio of the infarction and inhibited cell apoptosis in myocardial tissue. Furthermore, the AKT/GSK3β/β catenin signaling pathway was activated by GBE80. GBE80 injection effectively inhibited AMI-induced myocardial damage and in vitro H2O2-induced cardiomyocyte cytotoxicity by activating the AKT/GSK3β/β-catenin signaling pathway.